Historic Homes not on Court Street - Brooks County Museum and Cultural Center, Brooks County (Brooks County Museum and Cultural Center, 2013)
Historic Homes not on Court Street. (1874-2013). CA-009-005: Brooks County Museum and Cultural Center, 1874-2013 series. Quitman Brooks County Museum and Cultural Center Collection.
Historic Homes not on Court Street. (1874-2013). 1 electronic record (PDF), 21.0 MB (22,100,168 bytes).
Keywords: Quitman, Ga.; Brooks County (Ga.); Architecture; Housing; Homes